Evaluation of the Syntax Gap in Problem-Based Learning (PBL) and Science Literacy: A Multi-Case Analysis of Madrasah Science Teacher Supervision Results - Pipi Deswita; Rahma Dani; Azizah Rahmy; Festiyed Festiyed; Skunda Diliarosta; Fatni Mufit (Journal of Innovative Physics Teaching, 2026)
The low achievement of students' science literacy in Indonesia demands a radical instructional evaluation of innovative learning models such as Problem-Based Learning (PBL) at the school level. This study aims to deeply analyze the phenomenon of the syntax gap in the PBL model based on empirical data from the academic supervision of science teachers in madrasahs. Using a qualitative approach with a multi-case study design, this research examines teaching module documents, supervision recordings, and student scientific competency achievement sheets in two cases of science teachers at MTsN 17 Tanah Datar. The results of the cross-case analysis prove the existence of persistent procedural discrepancies between the written scenarios and classroom realizations, with an average implementation gap of the syntax ranging from 30.2% to 38.4%. The sharpest decline in teaching performance was consistently found in critical phases, particularly during the solution development stage and joint evaluation with students. The impact of the syntax gap directly affects the weak mastery of scientific literacy among students, which remains in the moderate to low category, especially in the aspects of scientific reasoning and evidence-based decision-making. These findings underscore the importance of reconstructing the paradigm of academic supervision from merely a formal administrative instrument to a continuous clinical evaluation function in order to uphold the pedagogical quality of science teachers in the field.